A muscle stem cell for every muscle: variability of satellite cell biology among different muscle groups - Randolph, Matthew E.; Pavlath, Grace K. (Frontiers in Aging Neuroscience, 2015)
The human body contains approximately 640 individual skeletal muscles. Despite the fact that all of these muscles are composed of striated muscle tissue, the biology of these muscles and their associated muscle stem cell populations are quite diverse. Skeletal muscles are affected differentially by various muscular dystrophies, such that certain genetic mutations specifically alter muscle function in only a subset of muscles. Additionally, defective muscle stem cells have been implicated in the pathology of some muscular dystrophies. The biology of muscle stem cells varies depending on their embryologic origins and the muscles with which they are associated. Here we review the biology of skeletal muscle stem cell populations of eight different muscle groups. Understanding the biological variation of skeletal muscles and their resident stem cells could provide valuable insight into mechanisms underlying the susceptibility of certain muscles to myopathic disease.